Impact of a Punching Process on the SyRM Iron Loss: SPICE Model as an Effective Tool for Iron Loss Modeling - Zbigniew Gmyrek (MDPI AG, 2021)
Many technologies for cutting the magnetic laminations, from which electric motors cores are built, change material properties, among which are magnetizability and iron loss, thus affecting the motor parameters such as motor efficiency. This problem is particularly important for low-power motors, in which the dimensions of the magnetic circuit elements are relatively small. The correct estimation of the motor efficiency is important as early as at its design stage. This is possible when the correct material characteristics are used. This knowledge and analytical model enabling fast estimation of material properties (depending on the actual size) are necessary for engineers, who design electrical motors by analyzing many solution variants in a short time. The author proposes an analytical model of changing material properties, implemented in SPICE software. Its effectiveness was compared with measurement results while being a competitive solution in relation to other analytical models. The proposed SPICE model allowed evaluating material properties for lamination of any width. In the end, the knowledge concerning the material properties was used to calculate the iron loss in the stator of the SyRM motor, showing the need to use the material characteristics calculated for the specified width of the core piece.